DENSIDADE POPULACIONAL DE HÍBRIDOS DE MILHO EM DIFERENTES ÉPOCAS DE SEMEADURA NA REGIÃO DE GUARAPUAVA – PR - SZCESNY, LUCIANA STREMEL (2016)
Proper fit between the choice of the hybrid, the sowing time and the population density is among the most important practices applied to achieve the highest grain yield in maize. In order to evaluate the effect of different population densities of corn and sowing dates on the morphological characteristics and production of corn hybrids in the region of Guarapuava, an experiment was conducted in the IAPAR’s experimental field in Guarapuava - PR. The experiment was conducted in 2013/2014 crop in field conditions in the area under no-tillage in the straw. The experimental lineation was a randomized blocks, with Split-split plot with three replications, being the sowing time, the main portion; the sub plot, the hybrid; and sub-sub plot, the population density. Eight corn hybrids were studied (2A 550 HX, 32R48 H, AG 8025 PRO2, AS 1656 PRO2, BG7051 H, CELERON TL, DKB 240 PRO 2 and NS 56 PRO), in four population densities (55.000, 70.000, 85.000 e 100.000 plants ha-1) and in three sowing dates ((Sep 7th, Sep 28th and Oct 19th). The different population densities affected the morphological characteristics: leaf area index, stem diameter, plant height and ear insertion height; and production parameters: number of grains per ear, number of grains per row, ear index, thousand grains weight and grain yield. The maximum yield was obtained in the density of 97.000 plants ha-1; the sowing dates affected the morphological characteristics: leaf area index, plant height and ear insertion height; and production parameters: number of grains per ear, number of grains per row, ear index and thousand grains weight; there were differences among hybrids for all morphological characters and production factors studied. The hybrids AG 8025 PRO 2, AS 1656 PRO2 and DKB 240 PRO 2 showed higher yield than the others, regardless of the sowing time and density.